National green tribunal and environmental governance - Chouhan, Giriraj Singh (Bihar Journal of Public Administration)
With a view to ensure speedy disposal of environment related disputes and delivery of environmental justice, the National Green Tribunal (NGT) was established by law. It was expected that the Tribunal would facilitate the environmental governance in India. Thus, it becomes an imperative to examine the functioning of and delivery of environmental justice by NGT in the context of strengthening environmental governance. The present paper intends to examine the NGT in the context of its structure, functions, jurisdiction and setting legal principles in disposal of the related cases and assesses its performance in relation to the environmental governance of India. Based on the secondary sources of data collection, the paper finds that the Tribunal has been successful, during the last decade, in bringing the environmental issues on political agenda and sensitizing governmental agencies in addition to delivery of environmental justice.- Reproduced
Keywords: National green tribunal, Environment, Governance, Justice delivery, India